Effect of the Degree of Hydrolysis on Nutritional, Functional, and Morphological Characteristics of Protein Hydrolysate Produced from Bighead Carp (Hypophthalmichthys nobilis) Using Ficin Enzyme - Kamal Alahmad (Foods, 2022)
The production of fish protein hydrolysates from bighead carp (Hypophthalmichthys nobilis) using ficin enzymes was achieved in optimal conditions of 3% enzyme/substrate ratio, 40 °C temperature, and pH 6. Three different hydrolysis times, 1, 3, and 6 h, were investigated, and their degree of hydrolysis (DH) values were 13.36%, 17.09%, and 20.15%, respectively. The hydrolysate yield values increased with DH increase, and the highest yield was obtained at DH 20.15%. The crude protein content increased from 80.58% to 85.27%, and amino acid compositions increased from 78.33% to 83.07%. The peptides formed during hydrolysis indicated low molecular weight that might improve functional characteristics of fish protein hydrolysates, including protein solubility, which ranged from 84.88% to 95.48% for all hydrolysates. The thermal degradation of hydrolysates occurred from 160 to 168 °C with intensive endothermic peaks. Results revealed that oil holding capacity was higher at DH 13.36%; water holding capacity was higher when DH increased. Hence, fish protein hydrolysates (FPH) from bighead carp have improved functional properties, and can be utilized as supplements and excellent protein sources in various uses in food applications.